“Integrating National Values in Visual Arts through Drawing Activities” - Rustamov Axtam Muxtorovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the integration of national values and traditional art motifs into visual arts education through drawing activities. It examines how these practices help students develop creative thinking, visual literacy, and cultural awareness. The study emphasizes the pedagogical importance of combining traditional elements with modern drawing exercises to enhance students’ artistic and cognitive competencies.